Topical Halometasone Reduces Acute Adverse Effects Induced by Pulsed Dye Laser for Treatment of Port Wine Stain Birthmarks - Gao, Lin; Qian, Linhan; Wang, Li; Li, Kai; Yin, Rong; Wang, Yanting; Kang, Hanmei; Song, Wenting; Wang, Gang (Journal of Lasers in Medical Sciences, 2017)
Introduction: Pulsed dye laser (PDL) for treatment of port wine stain (PWS) usually causes some acute adverse effects, including pain, erythema, scabbing and swelling. This study aimed to determine whether topical halometasone can be used to reduce these acute adverse effects for post-PDL care of patients. Methods: A total of 40 PWS subjects were enrolled in this study and randomly assigned into two regimens: PDL alone and PDL + halometasone. All subjects were given a single treatment of PDL with wavelength of 595 nm, fluence of 8.0 13.5 J/cm2, pulse duration of 0.45 20 ms (We mainly used purpuric pulse duration for PWS) and spot size of 7 mm. Subjects in the PDL + halometasone group received topical application of halometasone daily for 3 days. Subjects were followed-up on days 3, 7 and one month post-PDL to evaluate the reduction of adverse effects. Results: Subjects in the PDL + halometasone group had significantly improved erythema and scab scores and had less erythema duration days as compared to those in the PDL alone group. Topical halometasone also showed a decrease in pain index among subjects, but was statistically insignificant. Topical halometasone did not affect the ultimate efficacy of PDL treatment for PWS. Conclusion: Topical halometasone can significantly reduce acute adverse effects induced by PDL for treatment of PWS birthmarks, thus providing a safe and efficacious solution for post-PDL care of PWS patients.